Point Blank - Horowitz, Anthony 1955- (New York Speak, 2006)
Fourteen-year-old Alex continues his work as a spy for the British MI6, investigating an exclusive school for boys in the French Alps.
Keywords: Spy stories; Cloning -- Juvenile fiction; Schools -- Juvenile fiction; Orphans -- Juvenile fiction; Alps, French (France) -- Juvenile fiction; France -- Juvenile fiction; England -- Juvenile fiction